Analysis of the length of stay of tourists in Mataram City - Suwardi, Didik; Permata Cita, Fitria; ,, Jumaidin; ., Afifudin (Akademi Komunitas MAPINDO, 2024)
West Nusa Tenggara (NTB) Province is one of the provinces in Indonesia which in its development istargeted to become a national tourism gate with other provinces in the Nusa Tenggara region. NTB Provincewith the tagline